Tramadol Poisoning: A Systematic Review of Studies in Iran - Akhavan, Reza; Soroosh, Davood; Habibzadeh, Seyed Reza; Maleki, Fatemeh; Rayat Dost, Esmaeil; Teimouri, Ali; Foroughian, Mahdi (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: According to statistics, tramadol use is extremely prevalent in Iran. Besides, tramadol overdose is mostly observed in young individuals. Given the significance of this issue and the increasing prevalence of tramadol use in Iran, this study aimed to systematically review tramadol poisoning in Iran. Methods: In this review, a search was conducted in Persian databases of IranMedex, SID, Medlib, Magiran, as well as Google Scholar using the keywords of “poisoning and tramadol” without a time limitation. Results: Some of the main issues related to tramadol poisoning were as follows: the majority of cases consumed tramadol to commit suicide; most tramadol consumers were aged below 30 years; the majority of patients with tramadol poisoning were single and male; tramadol was mostly used orally; in most studies, patients were hospitalized for >24 hours; the majority of patients concomitantly took other medications with tramadol; in most studies, patients had a history of tramadol use; most studies reported a relationship between tramadol dose and seizures, and the most common cause of hospital referral was decreased consciousness level. Conclusion: Tramadol misuse and poisoning could lead to seizures and often death. Besides, most cases with tramadol poisoning were aged below 30 and consumed tramadol to commit suicide. Thus, it is crucial to improve the youth’s awareness about tramadol use, develop methods to prevent suicides, and limit access to this drug, especially in young adults.